A Holistic Strategy to Improve Teacher Engagement through Trust, Knowledge Management, and Organizational Culture in Private Vocational Schools in Bogor Regency - Taufiq Ismail, Yosa; Sri Setyaningsih, Sri Setyaningsih; Hardhienata, Soewarto (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Teacher engagement is a critical factor in ensuring the sustainability and quality of learning outcomes, especially in private vocational schools that face unique challenges in resource management and organizational dynamics. This study aims to propose a holistic strategy to improve teacher engagement through the integration of trust, knowledge management, and organizational culture. Using a mixed-method approach, data were collected from teachers and school administrators in private vocational schools in Bogor Regency. The findings reveal that trust between teachers and management fosters psychological safety and commitment; knowledge management enhances collaboration and continuous learning; while a supportive organizational culture strengthens motivation and professional identity. The interaction of these three dimensions creates a synergistic effect that significantly improves teacher engagement. This study contributes both theoretically and practically by offering a comprehensive framework for educational leaders to design policies and interventions that foster trust, optimize knowledge-sharing practices, and cultivate an inclusive organizational culture. The results highlight that a holistic and integrated strategy is essential to sustain teacher engagement and improve the overall performance of private vocational schools in Indonesia.